Early Surgical Management of Large Scalp Infantile Hemangioma Using the TopClosure® Tension-Relief System. Issue 47 (November 2015) - Zhu, Zhanyong; Yang, Xilin; Zhao, Yueqiang; Fan, Huajun; Yu, Mosheng; Topaz, Moris
Abstract : Abstract: Infantile hemangiomas (IHs) are the most common benign vascular neoplasms of infancy and childhood. The majority do not need medical intervention. However, large ulcerated scalp IHs may lead to fatal bleeding as well as severe cosmetic disfigurement that indicate early surgical excision, inflicting substantial surgical risks, with short- and long-term morbidity. The TopClosure Tension-Relief System (TRS) is an innovative skin stretching and wound closure-secure system that facilitates primary closure of relatively large skin defects. This system has been shown as a substitute for skin grafts, flaps, or tissue expanders. We describe a case of a giant IH of the scalp usually requiring a complex surgical approach, which was immediately primarily closed applying the TRS. A 3-day-old female infant presented with a giant scalp hemangioma at birth that rapidly grew in the neonatal period with early signs of ulceration. The patient underwent surgical resection of the giant scalp hemangioma with immediate primary closure of the defect using the TRS. Surgical procedure and postoperative period were uneventful. Early surgical resections of IHs at infancy carry substantial surgical risks and morbidity. This is the first reported case of early resection of a scalp hemangioma in the neonatal period, with successful immediate primary closure by application of stress-relaxation technique through the TRS. The application of the TopClosure TRS in this age group has significant advantages. It reduces the complexity and length of surgery, reducing blood loss, eliminating donor site morbidity, improving wound aesthetics, and minimizing the need for future reconstructive procedures.